2007
DOI: 10.4049/jimmunol.178.1.557
|View full text |Cite
|
Sign up to set email alerts
|

B Cell Clonal Expansion and Somatic Hypermutation of Ig Variable Heavy Chain Genes in the Synovial Membrane of Patients with Osteoarthritis

Abstract: Inflammatory mediators have been explored as possible factors in the initiation and/or progression of osteoarthritis (OA). This study shows that synovial infiltration by B lymphocytes is present in almost half of the knee OA cases. The degree of B lymphocyte infiltration is associated with more pronounced synovial inflammation and with the presence of plasma cells and lymphoid follicles in more severe cases. To examine whether these B cells are merely bystanders or could be involved in the pathogenesis of OA, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
31
0
1

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 49 publications
7
31
0
1
Order By: Relevance
“…1B), independently of potentially confounding factors such as the MHC background (HLA-DR shared epitope) and the presence of intracellular citrullinated proteins (data not shown) (31,32). These data confirm and extend our previous observations (26,28) showing that ectopic lymphoid neogenesis in the synovial membrane is neither restricted to nor preferentially associated with autoantibody positive rheumatic conditions.…”
Section: Synovial Lymphoid Neogenesis Is Not Restricted To Rasupporting
confidence: 80%
See 2 more Smart Citations
“…1B), independently of potentially confounding factors such as the MHC background (HLA-DR shared epitope) and the presence of intracellular citrullinated proteins (data not shown) (31,32). These data confirm and extend our previous observations (26,28) showing that ectopic lymphoid neogenesis in the synovial membrane is neither restricted to nor preferentially associated with autoantibody positive rheumatic conditions.…”
Section: Synovial Lymphoid Neogenesis Is Not Restricted To Rasupporting
confidence: 80%
“…A mucosal B cell lymphoma and peripheral blood cells from a healthy individual were used as positive and negative control. Using exactly the same approach on OA synovial tissue, we recently demonstrated that the number of analyzed sequences is sufficient to evaluate clonal expansion and affinity maturation (28).…”
Section: Immunglobulin Variable H Chain Gene Sequencingmentioning
confidence: 99%
See 1 more Smart Citation
“…32 and Figure 6C in the present study). As a consequence, B cells may expand clonally and hypermutate somatically in the presence of OA FLS (41).…”
Section: Discussionmentioning
confidence: 99%
“…Analysis of the Ig V H gene was performed as described elsewhere (37,43). Ig V H and VDJ genes were amplified by PCR and ligated into the pGEM-T vector (Promega, Madison, WI) and transfected into Escherichia coli DH5␣.…”
Section: Methodsmentioning
confidence: 99%